Karakteristik Atenuasi Seismik di Pulau Sumba Berdasarkan Analisis Gelombang Coda - Ayu Puput Ariyanti; Titi Anggono; Aditya Dwi Prasetio; Kartika Hajar Kirana (Postgraduate, University of Mataram, 2025)
Coda wave data from four stations are to understand seismic attenuation on Sumba Island. Specifically, we estimate the quality factor at 1 Hz (Q₀) and its frequency dependence (η) across multiple window lengths (20–120 s) and frequency bands (1–7 Hz) using waveform data from 394 local earthquakes. The aim is to evaluate how these parameters reflect crustal heterogeneity and tectonic activity. Results show that Q₀ increases with window length, indicating that coda waves progressively sample deeper and more homogeneous layers, while high η values at shorter windows suggest significant near-surface heterogeneity. These findings highlight a depth-dependent variation in seismic attenuation and structural complexity. The study reveals spatial variability, with MELO station showing anomalously high Q₀ values, likely due to localized site conditions or deeper structural influences. Sumba’s location within the tectonically active Sunda-Banda arc transition zone further supports these observations. The combination of low Q₀ and high η values confirms high tectonic activity, and the use of coda wave attenuation analysis offers a reliable, parameter-based framework for assessing seismic hazard potential in regions with complex geodynamics. This work fills a research gap by providing empirical data and interpretation for a previously underexplored area in eastern Indonesia.